Rauschenberg's Modern Infernos for Life Magazine. (2nd April 2016) - Smith, Graham
Abstract : In 1965 the American magazine Life published "A Modern Inferno, " a work commissioned from Robert Rauschenberg (1925–2008) to commemorate the 700th anniversary of the birth of the Italian poet Dante Alighieri (1265–1321). This work was inspired in part by the first canticle of Dante's celebrated Divine Comedy – the Inferno – which contains 34 cantos describing the torments of Hell. Rauschenberg made two prototypes for the Life feature, each of which comprises two panels. To create those, Rauschenberg used photographs selected in large part from past issues of Life and from its archives. This paper aims first to situate "A Modern Inferno" in the history of the reception of Dante within the United States. Secondly, it intends to place the Life feature and the studies for it in relation to Rauschenberg's immediately preceding work, emphasising its importance in his development of what art critic Rosalind Krauss had termed a "newly 'photographic' medium." To understand the historical significance of Rauschenberg's compositions, the paper also seeks to identify the characters and events illustrated in the photographs contained in them. Moreover, it considers how Rauschenberg deployed this subject-matter in order to represent the evil that occurred in much of the twentieth century. It is argued that some of these passages display affinities with the narrative of Dante's Inferno . Overall, however, relationships between Rauschenberg's compositions and the horrors of the Inferno are sweeping and metaphorical rather than literal. The paper concludes by touching on other elements from Dante's poetry that appear in works that Rauschenberg made in the years immediately after the Life commission.